Building Character through the Internalization of Moral Values in Learning from the Risalah Nur: A Case Study at Yasrib Islamic Boarding School, Soppeng Regency - Reski, A. Titin; Usman, Syahruddin; Afifuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
Education plays a strategic role in shaping students’ character and moral development, particularly amid the challenges of modernization that tend to erode traditional moral values. This study aims to examine the processes, methods, and outcomes of internalizing moral education values through the teaching of the Risalah Nur at Yasrib Islamic Boarding School in Soppeng Regency. This research employed a qualitative method using a case study approach. Data were collected through in-depth interviews, observations, and document analysis. Purposive and snowball sampling techniques were used to select participants. Data analysis focused on identifying patterns and meanings related to the internalization of moral values in students’ daily lives. The findings indicate that the internalization of moral values is implemented through both formal and informal learning activities, including the practice of religious rituals, exemplary conduct demonstrated by male and female religious teachers, and the cultivation of a disciplined dormitory life. The learning methods are contextual and reflective, enabling values such as sincerity, patience, and responsibility to be effectively instilled. This internalization process has a positive impact on improving students’ moral attitudes toward Allah SWT, themselves, others, and the environment. Therefore, learning the Risalah Nur significantly contributes to the development of students’ noble character. Abstrak: Pendidikan memiliki peran strategis dalam membentu karakter dan akhlak peserta didik, terutama ditengah tantangan modernisasi yang menggeser nilai-nilai moral. Penelitian ini bertujuan untuk mengkaji proses, metode, dan hasil internalisasi nilai-nilai pendidikan akhlak dalam pembelajaran kitab Risalah Nur di Pondok Pesantren Yasrib kabupaten Soppeng. Penelitian ini menggunakan metode kualitatif dengan jenis studi kasus. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi. Teknik pengambilan sampel menggunakan purposive sampling dan snowball sampling. Analisis data dilakukan untuk memahami makna dan pola internalisasi nilai akhlak dalam kehidupan santri. Hasil penelitian menunjukkan bahwa internalisasi nilai akhlak dilaksanakan melalui pembelajaran formal dan nonformal seperi pembiasaan ibadah, keteladanan ustadz dan ustadzah, dan pembinaan kehidupan asrama. Metode pembelajaran bersifat kontekstual, reflektif, sehingga nilai-nilai seperti keihklasan, kesabaran, tanggung jawab dapat terlaksana dengan baik. Internalisasi tersebut berdampak positif terhadap peningkatan akhlak peserta didik (santri) terhadap Allah SWT., diri sendiri, sesama manusia, dan lingkungan. Oleh karena itu, pembelajaran kitab Risalah Nur berkontribusi dalam pembentukan karakter santri yang berakhlak mulia.